Do Greek University Students Trust Social Media Regarding Science Related Issues? The Covid-19 Case - Vranias, Konstantinos; Kyridis, Argyrios (International Journal of Social Science Research, 2024)
This research aimed in revealing the trends of Greek universities’ student population in terms of their trust in social media, focusing on information and news related to scientific issues, and particularly on issues related to Covid-19. The sample of our study consisted of 557 people studying in various faculties of Greek universities throughout the country. Their answers in a questionnaire were analyzed using both descriptive and inferential statistics. Students’ answers revealed that despite they often resort to the use of social media and internet sources for informational purposes, they tend not to consider them as the most reliable source of obtaining information, regardless of the topic. They state that, contemplating the science and Covid-19 related information shared on social media platforms as unreliable and inaccurately presented, they try to cross-check it by drawing news from other media, a practice that contributes to them being able to distinguish fake news from true ones.